2005
DOI: 10.1101/gad.1304305
|View full text |Cite
|
Sign up to set email alerts
|

Replication checkpoint kinase Cds1 regulates Mus81 to preserve genome integrity during replication stress

Abstract: . Upon S-phase arrest by acute hydroxyurea treatment, Mus81 is not required for cell viability but is essential for recovery from replication fork collapse. Moreover, Mus81 undergoes extensive Cds1-dependent phosphorylation and dissociates from chromatin in hydroxyurea-arrested cells, thereby preventing it from cleaving stalled replication forks that could lead to fork breakage and chromosomal rearrangement. These results provide novel insights into how Cds1 regulates Mus81 accordingly when cells experience di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
143
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 66 publications
11
143
1
3
Order By: Relevance
“…Mek1 appears to be primarily responsible for the T218 and T422 phosphorylations of Mus81 as judged by the greater efficiency of 32 P incorporation by Mek1 than by Cds1, at least in vitro, when compared with the relative intensities of the Simply Bluestained bands (white arrows and arrowheads in Sup. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mek1 appears to be primarily responsible for the T218 and T422 phosphorylations of Mus81 as judged by the greater efficiency of 32 P incorporation by Mek1 than by Cds1, at least in vitro, when compared with the relative intensities of the Simply Bluestained bands (white arrows and arrowheads in Sup. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that Mus81 is phosphorylated by an unknown kinase on T239 (now T275) in the T-X-X-D motif in response to HU-induced replication arrest. 25,32 Here, we referred to their T239 as T275, according to the revised DNA sequence in the S. pombe database (http://www.genedb.org/genedb/Sear ch?name=SPCC4G3.05c&organism=pombe). We propose here that this unknown kinase is most probably Cds1 and/or Mek1, because either could directly phosphorylate Mus81 on T275 in vitro (Sup .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations